Spo0A Suppresses sin Locus Expression in Clostridioides difficile - Babita Adhikari Dhungel (American Society for Microbiology, 2020)
ABSTRACT Clostridioides difficile is the leading cause of nosocomial infection and is the causative agent of antibiotic-associated diarrhea. The severity of the disease is directly associated with toxin production, and spores are responsible for the transmission and persistence of the organism. Previously, we characterized sin locus regulators SinR and SinR′ (we renamed it SinI), where SinR is the regulator of toxin production and sporulation. The SinI regulator acts as its antagonist. In Bacillus subtilis, Spo0A, the master regulator of sporulation, controls SinR by regulating the expression of its antagonist, sinI. However, the role of Spo0A in the expression of sinR and sinI in C. difficile had not yet been reported. In this study, we tested spo0A mutants in three different C. difficile strains, R20291, UK1, and JIR8094, to understand the role of Spo0A in sin locus expression. Western blot analysis revealed that spo0A mutants had increased SinR levels. Quantitative reverse transcription-PCR (qRT-PCR) analysis of its expression further supported these data. By carrying out genetic and biochemical assays, we show that Spo0A can bind to the upstream region of this locus to regulates its expression. This study provides vital information that Spo0A regulates the sin locus, which controls critical pathogenic traits such as sporulation, toxin production, and motility in C. difficile. IMPORTANCE Clostridioides difficile is the leading cause of antibiotic-associated diarrheal disease in the United States. During infection, C. difficile spores germinate, and the vegetative bacterial cells produce toxins that damage host tissue. In C. difficile, the sin locus is known to regulate both sporulation and toxin production. In this study, we show that Spo0A, the master regulator of sporulation, controls sin locus expression. Results from our study suggest that Spo0A directly regulates the expression of this locus by binding to its upstream DNA region. This observation adds new detail to the gene regulatory network that connects sporulation and toxin production in this pathogen.